Advocacy on children victims of violence in the era of the covid-19 pandemic - Bambang Sukoco; Dewi Eko Wati; Dewi Kusuma Diarti; Moh. Indra Bangsawan; Arief Budiono; Arnold Tri Hantoro; Sandya Mahendra (ABDIMAS DEWANTARA, 2022)
Children are human beings and therefore respecting children's human rights is the same as respecting human rights. In addition, children are an inseparable part of the survival of human life and the sustainability of the entire nation and state. This community service aims to: 1). Describe the current legal basis for child protection; and 2). Describe legal protection for children in the era of the covid-19 pandemic. The results of the service show that the Covid-19 pandemic phenomenon has an influence on the formation and regulation of children's character in all aspects and conditions, including the current situation in the midst of the COVID-19 pandemic which demands a change in children's interactions with full activities at home. The intense presence of children at home has caused many violations of children'